Factors associated with pulmonary tuberculosis in older adults: A scoping review - Francisco de Assis Moura Batista; Juliana Iscarlaty Freire de Araújo; Fernanda Cunha Soares; Thalyta Cristina Mansano Schlosser; Clarissa Terenzi Seixas; Silvana Loana Oliveira-Sousa; Gilson de Vasconcelos Torres; Ana Elza Oliveira de Mendonça; Thaiza Teixeira Xavier Nobre (PLoS ONE, 2026)
Tuberculosis is an infectious disease with a substantial impact on public health, with the pulmonary form representing the most significant concern. The disease poses considerable risks to the elderly population, as it frequently manifests in conjunction with other age-related conditions, thereby complicating both diagnosis and clinical management. Several factors, including comorbidities, male sex, smoking, and alcohol consumption, may contribute to the development of the disease. This study aimed to identify, through a literature review, the main factors associated with pulmonary tuberculosis in older adults. A scoping review was conducted following the guidelines of the Joanna Briggs Institute and in accordance with the PRISMA-ScR extension for this type of study and was registered with the Open Science Framework. The research question was developed using the Population, Concept, and Context framework. Searches were conducted in electronic databases including PubMed, LILACS, Web of Science, Scopus, and Embase. Additionally, gray literature was retrieved from Google Scholar and the CAPES Theses and Dissertations Catalog. Health Sciences Descriptors (DeCS), along with their MeSH and Emtree equivalents, were used to identify the terms “Older Adults,” “Pulmonary Tuberculosis,” and “Risk Factors,” combined with Boolean operators AND and OR. Pulmonary tuberculosis was found to be strongly associated with older male individuals, those with a prior diagnosis of diabetes mellitus, smokers, alcohol users, individuals with close contact with active TB cases, and those with liver cirrhosis. The findings suggest that pulmonary tuberculosis is determined by multifactorial conditions, including those naturally associated with aging. The study underscores the need for targeted public health policies that integrate active surveillance, early diagnosis, and social support. The results provide a basis for evidence-based interventions aimed at controlling pulmonar tuberculosis in this vulnerable population.